Pengembangan Disiplin Ilmu di Institusi Pendidikan Teknologi dalam Membangun Budaya Informasi untuk UKM - Dicky Rezady Munaf (Jurnal Sosioteknologi, 2006)
The empowerment of the small and medium scale businesses (SMSB) through the employment of technologies are constrained by two factors: (a) the lack of SMSB capacity in adopting the technologies and (b) the less proactive efforts of the technology producers in promoting their technology products. The constraints of the SMSB are, among others, that they are lack of funds for their entrepreneurship, inconsistent in their entrepreneurship, lack of support from the mainstream industries, lack of conducive laws on the technology transfer for SMSB, and not accustomed to using information and data about relevant science and technology for SMSB. On the other hand, the technology providers are constrained by the fact that there has been no appropriate technology package for SMSB while the organization responsible for the information and data concerning science and technology has not yet detected the SMSB's needs of relevant technologies for their actual entrepreneurship activities. One of the ways to overcome the above-mentioned problems is to develop a network of information technology system and some assistance for the SMSB so that the information culture is established. The main factor that has a significant role in developing a network of information technology system and some assistance for the SMSB is the human resources of interrelated institutions. The institutions are, among others, science and technology institutions, SMSB (users), education/ training institutions, financial institutions, and policy-making institutions. Hence, the establishment of an academic discipline in science and technology/engineering academic institution is required to develop some significant values from every output of its technological process for the sake of the improvement of people's welfare. The phenomenon that there is a reciprocal relationship between science and technology discipline and humanities implies that the information being discussed should include not only the information on science and technology but also the information containing the social values needed by the people. The mechanism for establishing such reciprocal relationship has to take place continuously at both the level of SMSBs (users) and at the level of science and technology institutions.